1867: ¿“momento republicano”? - Campos Pérez, Lara (El Colegio de México, A.C., 2022)
This article analyzes the political debate on republicanism that was held in Mexico during the five months following Benito Juárez’s return to the country’s capital on July 15, 1867. It primarily uses leading articles in the contemporary press and, to a lesser degree, other texts such as speeches and political programs, which are interpreted in their original context. The goal is to determine if, during this period, there was a situation in Mexico analogous to the “Machiavellian moment,” as Pocock put it in the 1970s. That is, if, in the moment in which a republic stops being an ideal and becomes the country’s political reality, intellectuals and publicists who become disenchanted with the government’s behavior turn to the reformulation of principles and theories of a more or less republican stamp in order to propose responses that would allow for the moral and political stability of the republic to be maintained.